Taking sides. - Monk, Richard C. 1943- (McGraw-Hill/Dushkin, 2002)
This debate-style reader is designed to introduce students to controversies in race and ethnicity. The readings discuss issues such as social identities and cultural conflict, immigration, affirmative action and legal issues.